Optimization of lovastatin in solid-state fermentation using oil palm frond - Nur Fathin Shamirah, Daud; Farhan, Mohd Said; J. M., Ho (IOP Publishing, 2020)
Lovastatin plays a role in lowering the cholesterol level in the human blood, especially the bad cholesterol or low density lipoproteins (LDL). Concurrently, lovastatin increase the good cholesterol or high density lipoproteins (HDL), to prevent the formation of plaque inside the blood vessels. The objective of this research was to experimentally optimize the lovastatin compound produced by Monascus purpureus FTC5357 under solid state fermentation (SSF) using oil palm frond (OPF). In order to identify the optimal condition to produce lovastatin, four parameters which were pH, initial moisture content, peptone and potassium, were optimized using Box–Behnken design. Based on the ANOVA analysis performed, initial moisture content, potassium and peptone contributed significantly to the lovastatin production. Meanwhile, pH had the least impact to the lovastatin production.. Peptone pronounced to be the most contributed factor, as the lovastatin production increased with the increasing of peptone in the substrate. Under optimized condition (pH 5.50, moisture content at 60%, 3.40 g of potassium, and 3.30 g of peptone) maximum lovastatin yield was 45.84 µg/g. The lovastatin produced through SSF using OPF as a substrate by Monascus purpureus FTC 5357 has a great potential to be utilized as a source of lovastatin in future.